Pemanfaatan Sistem Informasi Geografis untuk Pengembangan Ruang Terbuka Hijau Kota Bandung - Angrini, Sisca Novia; Diem, Anson Ferdiant; Safitri, Della (Universitas Muhammadiyah Palembang, 2023)
Urban changes characterized by concrete and steel dominance have threatened the existence of green spaces in cities. Urban greening is crucial to address urban environmental issues. The city of Bandung, faces challenges of limited green spaces and suboptimal park management. The aim of this research is to examine and apply a park asset management model using the asset management approach and GIS. This approach aims to optimize park functionality and enhance the quality of Bandung's green spaces. The study adopts a descriptive approach with interview and field observation techniques. Park attribute data is collected through direct observation and organized in GIS format. Spatial analysis using GIS is conducted to identify park characteristics and potential management opportunities. By employing the asset management approach and GIS, relevant and significant park attributes for asset management can be identified. This information aids in making better park management decisions. Additionally, GIS enables spatial analysis to evaluate the strategic level of parks and optimize their utilization. The asset management approach and the implementation of GIS provide effective solutions for the development and management of Bandung's green spaces. By optimizing the use of park assets and applying asset management principles, it is expected to improve the quality of green spaces and provide greater benefits to the city's residents.